Phytochemical Composition, Antioxidant and Antifungal Activity of Thymus capitatus, a Medicinal Plant Collected from Northern Morocco - Amina Benoutman; El Hadi Erbiai; Fatima Zahra Edderdaki; El Khalil Cherif; Rabah Saidi; Zouhaire Lamrani; Manuela Pintado; Eugénia Pinto; Joaquim C. G. Esteves da Silva; Abdelfettah Maouni (MDPI AG, 2022)
Thymus capitatus is a Mediterranean endemic plant commonly known as "Zaïtra" in northern Morocco. As T. capitatus is widely used in traditional medicine and food, this present work aims to investigate the chemical compositions and biological activities of the T. capitatus leaves essential oil (TcLEO), acetonic (TcLAE), and methanolic extract (TcLME). The spectrophotometric determination demonstrated that T. capitatus is a natural source rich in phenolic contents (TPC) and flavonoid contents (TFC) and that TcLME revealed the highest TPC and TFC than TcLAE and TcLEO. The LC-MS analysis of phenolic compounds showed that paraben acid was predominant in both TcLME and TcLAE, followed by cinnamic acid and p-hydroxybenzoic acid. GC-MS analysis of the TcLEO revealed the presence of a total of 10 compounds, which were predominated by carvacrol. The antioxidant activity by ORAC was observed to be significantly higher in TcLEO and TcLAE than in TcLME. All samples used to assess DNA degradation effectively prevented DNA oxidation and, at the same time, had a prooxidant effect. The genotoxicity test showed that the T. capitatus were devoid of any mutagenic activity. Concerning antifungal activity, all samples were able to inhibit the growth of all microorganisms tested at low concentrations. TcLAE showed higher activity than TcLME, and in general, dermatophytes were more susceptible, being Microsporum canis the most sensitive one. Overall, the results obtained from this study confirm the wide uses of T. capitatus. Furthermore, the finding results suggest that the T. capitatus essential oil and extracts can be highly useful for pharmaceutical industries.